THE ROLE OF END CHILD PROSTITUTION, CHILD PORNOGRAPHY AND TRAFFICKING OF CHILDREN FOR SEXUAL PURPOSES (ECPAT) IN ADDRESSING THE CHILD’S COMMERCIAL SEXUAL EXPLOITATION (ESKA) IN INDONESIA (2011 – 2015) - Yohanes Benedicktus Meninu Nalele (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2019)
Commercial sexual exploitation of children is a social problem that has several categories. This issue is scattered in many countries, especially in Asian countries. Child’s commercial sexual exploitation or eksploitasi seksual komersial anak (ESKA) can ruin the future of the children who are victims, of which they are the successors of the nation. Childhood should be filled by playing and learning but changing with the dark. The role of government as the supreme authority of a country in overcoming the problem of ESKA looks not maximized. The purpose of this research is to find out the role of international organizations in addressing the ESKA problem. International organizations, in this case, are ECPAT or End Child Prostitution, child pornographic grapy, and Trafficking of Children for Sexual Purposes. How are their efforts and roles in overcoming ESKA and its cooperation with the Indonesian government, obstacles, and challenges faced? The benefits of this journal are useful in the development of International Relations, especially those involving the role of international organizations in addressing the problems of ESKA. The method used is descriptive – qualitative, where this method illustrates and analyzes the role of ECPAT as an international organization in addressing the ESKA in Indonesia (2011 – 2015).